2018
DOI: 10.1177/0361198118799705
|View full text |Cite
|
Sign up to set email alerts
|

Airfield Pavement Damage Evaluation Due to New-Generation Aircraft Wheel Loading and Wander Patterns

Abstract: This paper presents a stress-history-based approach to predict the deformation basins of airport pavements subjected to heavy aircraft loading applied in sequential wanders. Multi-depth deflectometer data from full-scale aircraft landing gear tests conducted at the National Airport Pavement Test Facility built by the Federal Aviation Administration are used to create individual pass residual deformation transverse profiles. The computed residual deformation profiles are further corrected for stress-history eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This interaction indicated a shuffling or rearrangement of the aggregate particles that reduced the strength of the unbound layer. More recently from the full-scale tests at the CC5 experiment with multi-depth deflectometer measurements at NAPTF, heaving of the pavement system and individual layers after the heavy gear traffic loading was observed under the centerline of the dual-wheel gear, which is at offset 3 in this study ( 17 , 26 ). In addition, the considerable heave was reported when both wheels of the loading module passed the outer offset location from the sensor location, which is offset 1 and offset 5 locations in this study.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This interaction indicated a shuffling or rearrangement of the aggregate particles that reduced the strength of the unbound layer. More recently from the full-scale tests at the CC5 experiment with multi-depth deflectometer measurements at NAPTF, heaving of the pavement system and individual layers after the heavy gear traffic loading was observed under the centerline of the dual-wheel gear, which is at offset 3 in this study ( 17 , 26 ). In addition, the considerable heave was reported when both wheels of the loading module passed the outer offset location from the sensor location, which is offset 1 and offset 5 locations in this study.…”
Section: Resultssupporting
confidence: 57%
“…The National Airport Pavement Test Vehicle (NAPTV) is a program-controlled rail-based test vehicle with two carriages that was built along with the test track. Each carriage in the vehicle can be equipped with up to five axles that can carry nine wheels ( 17 ). The testing vehicle has the maximum total load capacity of 1.3 million pounds (5.78 MN), which can be applied with various configurations of vehicle gear and wander sequences.…”
Section: Naptf Test Sectionmentioning
confidence: 99%
“…On average, the modulus from the second pass was 28.24% higher than that of the first pass. The previous NAPTF full-scale pavement tests reported that the vehicle passes with wander offsets caused an “anti-shakedown” effect in the unbound aggregate layer because of the upward dilative deformation caused by large horizontal stresses ( 58 ). Further, Kang et al observed a modulus decrease after the wheel pass with the wheel offset and a modulus increase after the wheel pass without the wheel offset via BE field sensor measurement ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Embedded sensors, such as strain gauges, pressure cells, multi-depth deflectometers, and inductive coil sensors, have been widely used in constructed full-scale pavement test sections to monitor pavement responses. A previous study on the influence of heavy aircraft loading on airport pavement base/subbase layers using embedded sensors has primarily focused on the deflection of the layers under repeated loading and vehicle wander, unveiling the effect of vehicle wander on the base layer and establishing layer deflection models (4)(5)(6)(7)(8). In addition to the deflection behavior, real-time measurements of pressures and deformations using embedded sensors enable the estimation of in situ moduli.…”
mentioning
confidence: 99%